Feeling for Our Robot Overlords: Perceptions of Emotionally Expressive Social Robots in Initial Interactions. Issue 2 (4th March 2021) - Craig, Matthew J. A.; Edwards, Chad
ABSTRACT: Human-to-human scripting accounts for a user's tendency in human-robot interactions (HRI) to utilize scripts just as they would if talking to another person. Can a robot's emotional verbal expression, however, impact perceptions and further elicit human-to-human scripting? The present study examines the effects of a robot's emotional expression of joy and sorrow on participant perceptions of anthropomorphism, animacy, likability, perceived intelligence, credibility, social presence, and uncertainty in an initial interaction. Results indicated that robot expressions of joy were rated significantly more likable, intelligent, credible, and socially present than expressions of sorrow. Implications for future research are discussed in light of our findings related to participant impressions of emotional robots and human-to-human scripting.